The activated newborn neurons participate in enriched environment induced improvement of locomotor function in APP/PS1 mice. Issue 7 (15th May 2019) - Wang, Hualong; Li, Qiongqiong; Tang, Huidong; Ding, Jianqing; Xu, Nanjie; Sun, Suya; Chen, Shengdi
Abstract: Introduction: Alzheimer's disease (AD) is an age‐related neurodegenerative disorder. One of the pathological features of AD is neuronal loss in brain regions associated with cognition, particularly the hippocampus. An enriched environment (EE) can facilitate neuronal plasticity and improve behaviors such as emotion, motor function, and cognition in AD. Methods: After APP/PS1 mice were exposed to EE at an early stage (2 months of age), elevated plus maze performance and contextual fear conditioning were tested, and neurogenesis and the extent of activation in the hippocampus were observed. Results: The results showed that, compared with that in the mice that experienced a standard environment, the cognition of the mice exposed to EE, as measured by contextual fear conditioning, was not statistically significant. However, based on their performance in the elevated plus maze, the index was increased in the mice, especially the APP/PS1 mice, exposed to EE. Consistent with the behavioral changes, the APP/PS1 mice exposed to EE showed an increased number of c‐Fos‐positive neurons and elevated neurogenesis in the dentate gyrus (DG) area. In addition, the activation of newborn neurons did not occur in the other three groups. Conclusions: These results indicate that the activation of newborn neurons may participate in the improvement of behavioral performance in APP/PS1 mice after EE. Abstract : After exposure to EE in APP/PS1 mice at the early stage of 2 months of age, the elevated plus maze and context fear condition were tested in those mice, followed by the observation of neurogenesis and activation extent in hippocampus. The results indicate that the activation of newborn neurons may participate in the improvement of behavioral performance in APP/PS1 mice after EE.